THE NATIONAL-CULTURAL SEMANTIC COMPONENT OF CARESSING (Web of Teachers: Inderscience Research, 2024)
In the article, it is clear that the analysis of the national-cultural semantic component of the field of caressing in English and Uzbek languages was carried out, the units included in this field were studied from the point of view of equivalence.